2020
DOI: 10.1016/j.heliyon.2020.e05551
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Korean rice lines for their reaction to rice yellow mottle virus in Ghana

Abstract: Rice yellow mottle virus (RYMV) is the most damaging viral disease of rice in Africa and can cause yield losses of up to 100%. The objective of this study was to characterize newly introduced rice lines from Korea into Ghana for their reaction to RYMV infection. One hundred and seventy-two rice lines from Korea were screened for their level of resistance RYMV in a screen house at Fumesua, Ghana. Four checks consisting of two highly resistant lines (Tog7291 and Gigante with rymv1-2 (resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…As further evidence, Banwo et al (2001) found that even only 4 individuals of pulla group determine the 80% of probability of RYMV infection, with a corresponding high yield loss (Asante et al, 2020) This is reflected by the rice production loss analyses (heatmaps), in which we find some countries to suffer high losses, with the greatest predicted for Liberia and Sierra Leone. Despite this data, these countries are reported to suffer less economic damage due to their cropping systems (uplands rice crops), which are less susceptible to pulla group attack (Mogga et al, 2012;Oludare et al, 2016;Suvi, Shimelis & Laing, 2019).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As further evidence, Banwo et al (2001) found that even only 4 individuals of pulla group determine the 80% of probability of RYMV infection, with a corresponding high yield loss (Asante et al, 2020) This is reflected by the rice production loss analyses (heatmaps), in which we find some countries to suffer high losses, with the greatest predicted for Liberia and Sierra Leone. Despite this data, these countries are reported to suffer less economic damage due to their cropping systems (uplands rice crops), which are less susceptible to pulla group attack (Mogga et al, 2012;Oludare et al, 2016;Suvi, Shimelis & Laing, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Also, they represent an important vector of the RYMV in SSA (Bakker, 1971;Koudamiloro et al, 2015); moreover, Banwo et al (2001) report that if specimens of pulla group abundantly occur when an RYMV source is present, a vast spread of the virus is expected. Rice yellow mottle virus and can cause up to 80% -100% yield loss in some rice-cropping systems (Wopereis et al, 2013;Asante et al, 2020), with a decrease in the number of spikelets, the partial or total sterility of the rice panicles, and the death of the infected plant (Kouassi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Even though this virus can be transmitted through contact by many mechanisms ( Abo et al, 2000 ; Sarra et al, 2004 ; Traore et al, 2009 ), the presence of beetles is assumed to support long-distance transmission ( Fargette et al, 2006 ). As further evidence, Banwo et al (2001) found that even only four individuals of pulla group determine the 80% of probability of RYMV infection, with a corresponding high yield loss ( Asante et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…Also, they represent an important vector of the RYMV in SSA ( Bakker, 1971 ; Koudamiloro et al, 2015 ); moreover, Banwo et al (2001) report that if specimens of pulla group abundantly occur when an RYMV source is present, a vast spread of the virus is expected. Rice yellow mottle virus and can cause up to 80–100% yield loss in some rice-cropping systems ( Wopereis et al, 2013 ; Asante et al, 2020 ), with a decrease in the number of spikelets, the partial or total sterility of the rice panicles, and the death of the infected plant ( Kouassi et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…A single dominant resistant gene RYMV3 encoding NBS-LRR protein was identified from the O. glaberrima Tog5307 ( Pidon et al., 2017 ). Novel resistant alleles and accessions for RYMV2 and RYMV3 were identified by screening 268 O. glaberrima accessions and sequencing ( Pidon et al., 2020 ), and five new resistant germplasm were isolated from Korean rice lines ( Asante et al., 2020 ). The cloned genes with different resistant alleles will be useful to improve RYMV resistance, especially for the breeding program for the African continent.…”
Section: Viral Diseases and Available Genetic Resourcesmentioning
confidence: 99%